Exercise Therapies for Parkinson’s Disease: A Systematic Review and Meta-Analysis - Hyun-young Choi; Ki-Ho Cho; Chul Jin; JiEun Lee; Tae-Hun Kim; Woo-Sang Jung; Sang-Kwan Moon; Chang-Nam Ko; Seung-Yeon Cho; Chan-Yong Jeon; Tae Young Choi; Myeong Soo Lee; et al. (Parkinson's Disease, 2020)
Recently, rehabilitative exercise therapies have been described as an important method of overcoming the limitations of the conventional therapies for Parkinson’s disease. The present study aimed to evaluate efficacy and safety of exercise therapies for Parkinson’s disease. Randomized controlled trials that evaluated exercise therapies in patients with Parkinson’s disease until December 2016 were searched for in five electronic databases: PubMed, CENTRAL, EMBASE, OASIS, and CNKI. Eighteen studies (1,144 patients) were included. The overall methodological quality was not high. Patients who underwent exercise therapies exhibited statistically significant improvements in the total UPDRS, UPDRS II and III, Berg Balance Scale, preferred walking speed, and Timed Up and Go Test compared to patients who underwent nonexercise therapies. In comparison to patients who performed regular activity, patients who underwent exercise therapies exhibited statistically significant improvements in the total UPDRS, UPDRS II, and UPDRS III. Exercise therapies were found to be relatively safe. Exercise therapies might promote improvements in the motor symptoms of Parkinson’s disease. However, due to the small number of randomized controlled trials and methodological limitations, we are unable to draw concrete conclusions. Therefore, further studies with better designs will be needed.